Fire Weather Index assessment and visualization - Waidelich, Sigfrido (2019)
The Fire Weather Index (FWI) is extensively used in Argentina to support operative preventive measures for forest fires management. This index describes the moisture content of three different fuel types and the effect of the wind in the behaviour of fire. During last years our team developed a wildfire simulator with several functionalities requested by firefighters. In this work we report the spatial visualization of the FWI on our simulator, in order to describe the dependence of forest fire risks on FWI and fuel type of Northwest Patagonian forests in Argentina. This additional functionality allows the user to visualize the local spatial configuration of fire risk. The potential of this tool is that it would provide the FWI to be readily used in all fire stations in Argentina. Moreover, it could be taken as input information of a fire propagation model under development. In this sense, the need of modelling the impact of weather on the fuel becomes essential for the accuracy of forest fire simulations.